Study and Design Thailanna Style’s Showcase - Mungpanklang, Nabhapol; Seviset, Somchai; Ekawutwongsa, Songwut (Mediterranean Journal of Social Sciences, 2020)
The purpose of this research is to study the Lanna art form, design showcase in Lanna art style and evaluate the satisfaction of those interested in buying a Lanna style showcase. The Lanna art forms that we studied are Lung Piang, Fat-Short, Flora patterns, Red color, Dark brown-black and gold patterns. Also the wood that has been using is Teak wood material, which is medium softwood. When analyzed together with the conceptual framework to design a showcase of Lanna art style, with experts and professionals join the evaluation of draft design 3 sets 9 drafts and eliminate to 1 draft only in order to use it as a prototype. Use descriptive statistics to analyze and summarize data. The research found that showcase in Lanna art style, draft B which uses the design concept of Lanna art has overall result in the highest level ( = 4.62, S.D. = 0.52). Then this draft is taking to produce the prototype and evaluate the satisfaction, the research found that satisfaction level in terms of conservation, inheritance, and pride of wisdom in art and cultural is at the highest level ( = 4.41, S.D. = 0.69), followed by beauty. And characteristics has satisfaction level at high level ( = 4.25, S.D. = 0.78). Safety, functional, structural and material satisfaction is at a high level ( = 3.97, S.D. = 0.70).